Correction: Best-worst scaling preferences among patients with well-controlled epilepsy: Pilot results. - Samuel W Terman; Hélène E Aschmann; David W Hutton; James F Burke (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0282658.].